Assessing the impact of indoor air pollution on respiratory health: A survey of home residents in rural area - P. Rajkumar; B. Vijay Bhaskar (The Scientific Temper, 2024)
Particularly in residential settings people spend more time inside a house. It is a serious environmental health hazard. The purpose of this research is to evaluate how house occupants' respiratory health is affected by indoor air pollution. The study focuses on typical indoor contaminants, nitrogen dioxide (NO₂), carbon monoxide (CO), particulate matter (PM), and volatile organic compounds (VOCs). The research uses a survey-oriented approach to gather information from inhabitants in various housing situations, such as urban, suburban, and rural regions. The survey addresses the prevalence of respiratory symptoms and conditions (such as allergies, asthma, and chronic obstructive pulmonary disease). The presence of indoor pollution sources (such as cooking stoves, tobacco smoke, and chemical cleaners), residents' awareness and attitudes towards air quality. The gathered information is examined to find any relationships between the reported respiratory health problems and the amounts of indoor pollution. The research results shown that, there is a direct correlation between indoor pollution levels and the frequency of respiratory complaints. The research emphasises the importance of using air purifiers, better ventilation, and public education on reducing indoor pollution sources. According to the findings, improving indoor air quality is crucial for home occupants' respiratory health and general well-being.